Strategic-Operational Synergy: A Systematic Review of POAC–PDCA Integration for Enhancing Organizational Agility - Selvi, Evi; Supriyadi, Didit; Fadili, Dadan Ahmad; Rahma, Madjidainun; Chaerudin, Chaerudin (Eastasouth Institute, 2025)
In an era of business transformation marked by extreme volatility and the uncertainty of the strategic environment, modern organizations face ongoing pressure to achieve operational excellence while maintaining adaptive flexibility. The complexity of contemporary challenges demands the integration of managerial approaches that emphasize procedural efficiency and strategic responsiveness through the synergy of Planning, Organizing, Actuating, Controlling (POAC) and Plan-Do-Check-Act (PDCA). This study aims to systematically analyze POAC-PDCA integration to improve organizational agility, strategic effectiveness, and sustainable adaptability in a dynamic business environment. The research method used Systematic Literature Review (SLR) with the PRISMA protocol, analyzing 12 high-quality Scopus journals for the period 2019-2024 from five main academic databases. The results showed that the POAC-PDCA integration was able to increase time responsiveness by up to 70%, operational flexibility through a 53% reduction in setup time, and measurable strategic adaptability across the health, manufacturing, port, and waste management sectors. The conceptual model developed positions POAC as the structural foundation that strengthens the PDCA cycle as a sustainable diagnostic-corrective mechanism. The study's conclusions affirm that successful integration is achieved through vertical alignment, horizontal integration, systematic feedback loops, and a culture of continuous improvement, requiring technological support and organizational mindset transformation to achieve the optimal balance between operational stability and strategic flexibility.